W poszukiwaniu teoretycznoprawnych źródeł konieczności proceduralnego zabezpieczania materialnych gwarancji praw człowieka. Analiza założeń Johna Finnisa i Roberta Alexy’ego - Czepek, Jakub (PRAWO i WIĘŹ, 2026)
The issue of positive obligations, and in particular procedural obligations, is very important in the sphere of contemporary international protection of individual rights. Positive obligations include substantive and procedural obligations. An extremely important element of this construct is the safeguarding of substantive guarantees by procedural means. Supplementing substantive rights with effective investigation procedures ensures its practical dimension and protects such law from becoming theoretical and illusory. Leaving any legal guarantee without procedural safeguards will prevent or, at best, significantly hinder its use by the entitled entity. The quality of procedural measures is also important, as they should fulfil their role effectively in order to ensure the real possibility of using the appropriate mechanisms and procedures to secure the substantive guarantee. The aim of this study is to examine the views that accurately reflect the need for procedural safeguards for substantive guarantees of individual rights. From the perspective of international human rights law, the aim is therefore to present views that formulate the theoretical and legal basis for the creation of positive obligations, especially procedural obligations, with regard to fundamental individual rights. In this regard, the views of Robert Alexy and John Finnis are particularly important. Both authors seem to reflect in the broadest sense the nature and theoretical basis of the need to supplement substantive guarantees with procedural mechanisms.